IMPLEMENTASI KONSELING BERBASIS NILAI DALAM MENINGKATKAN MORALITAS SISWA DI MTSN 1 BANJAR - Miftahul Aula Sa’adah; Hamdan Juwaeni (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
This study aims to explore the implementation of value-based counseling in improving student morality at MtsN 1 Banjar. Through a qualitative approach with a case study method, this research involves in-depth interviews, observation, and documentation to understand how Guidance and Counseling (BK) teachers apply value-based counseling methods in shaping student character. The results show that storytelling, group discussion, self-reflection, and role-playing methods can help students understand and internalize moral values, such as honesty, discipline, and empathy. Collaboration between counseling teachers, parents, and subject teachers is also a key factor in building a consistent environment in instilling moral values to students. The positive impact is seen in the improvement of honesty, discipline, and caring for others, although there are still challenges such as time constraints and parental involvement. Overall, the implementation of value-based counseling shows an improvement in shaping students' morality, so this counseling is useful as an effort to build a generation with strong character and based on moral values.